Strategy for Utilizing TikTok Social Media as a Digital Marketing to Increase Sales at the Infarm Surabaya Brand - Dhani Rizky Pradana; Sonja Andarini (Lavish Opulent Education, 2025)
This research has the aim of analyzing the Digital Marketing Strategy at Brand Infarm Surabaya using the TikTok platform, which is a business in the plantation sector, namely selling gardening needs. The research method used descriptive qualitative using SWOT analysis techniques with data collection techniques from in-depth interviews, observation, and documentation containing related digital marketing strategies, with the aim of identifying strengths, weaknesses, opportunities, and threats with the SWOT analysis method at the Infarm Surabaya brand. The informants in this study are the owner, employees, and consumers of the Infarm brand. The results of research using IFAS show that the Infarm brand has a strength score of 2.94 and a weakness score of 0.38. Meanwhile, the EFAS results show an opportunity score of 2.71 and a threat score of 0.46. Judging from the SWOT diagram, the Infarm brand is in quadrant I with a value of (X;Y) (2.56:2.25), which shows that the Infarm brand uses the SO (Strength+Opportunity) strategy, which uses strengths to create an opportunity. The strategy that can be used is an aggressive strategy to increase sales.